Culinary tourism as a destination attraction : an empirical examination of destinations' food image. - Ab Karim, Shahrim; Chi, Christina Geng-Qing (Taylor & Francis, 2010)
This article illustrates the food image of France, Italy, and Thailand, countries known for their popular cuisine. An online survey was conducted; the population consisted of members of online travel and food groups from Yahoo.com and MSN.com. A total of 294 individuals responded to the online survey. A series of multiple regressions were conducted to determine (a) the relationship between destinations' food image and travelers' visit intention, and (b) the relationship between information sources and travelers' purchase decisions. The results revealed that in general, Italy had the most favorable food image and the highest potential to be visited in the future. Significant positive relationships were found between food image and visit intentions. The study also confirmed that travelers' purchase decisions were significantly influenced by different types of information sources. Conclusions and implications were drawn based on the research findings. This information would be particularly useful for destinations interested in promoting culinary tourism.